Tubercular Retropharyngeal Abscess With Pott’s Disease in an Elderly Male Patient - Thomas, Kiren (Cureus, 2020)
Retropharyngeal abscess (RPA) is a life-threatening emergency due to its potential to cause airway compression. It is rare in the elderly and occurs mostly in immunocompromised patients, or as a complication of instrumentation. We are reporting the case of a 70-year-old male who presented with sudden onset breathing difficulty with a history of dysphagia for three months. The clinical examination revealed a bulge in the posterior pharyngeal wall. A lateral-view radiograph of neck revealed retropharyngeal soft tissue density with carious spine. The patient was successfully treated by trans-oral incision and drainage of the abscess under local anesthesia. Diagnosis of tuberculosis was confirmed by positive acid-fast staining and cartridge-based nucleic acid amplification test (CBNAAT). The patient improved significantly following the initiation of anti-tubercular therapy.